Model Akuntansi Sederhana Bagi UMKM (Studi Kasus Pada Panglong Muslim Laut Dendang Percut Sei Tuan) - Rapika Rapika; Kusmilawaty Kusmilawaty (-, 2022)
The purpose of this service activity is to provide competency direction and understanding in determining and compiling income statements for UMKM at Muslim Panglong. This is carried out to help solve the problems faced by UMKM owners regarding their lack of understanding of accounting. Service activities are devoted to assisting in the preparation of income statements. The service program is carried out in several stages, starting with material presentation, practical simulation using the "accounting card book", and the last stage is stabilization through question and answer. Suggestions from this activity are the need for further training for the preparation of other financial statements such as cash flow statements and statements of financial position. The method used in this activity is qualitative research, with the research subject being Muslim Panglong